Wealth redistribution between stakeholders - JIRARI, Samia; El Kabbouri, Mounime; Rigar, Sidi Mohamed (Archives of Business Research, 2020)
Corporate social responsibility (CSR) is a very popular concept that hits the headline recently, companies face the obligation, not only to maintain their viability to ensure the sustainability of their business by continuing to create value, but to adopt a mode of governance that combines interests of all stakeholders. A CSR strategy is becoming more and more an obligation than just a wise choice. The strong involvement of Moroccan companies in CSR strategies is not by coincidence; but fits perfectly into the Kingdom's strategy, which adheres to the principles of sustainable development and CSR, for a sustainable economy and an inclusive growth. The purpose of this empirical study is to examine the shareholder’s engagement and the degree of involvement in CSR strategy, of a sample of 45 Moroccan companies listed on the Casablanca Stock Exchange and belonging to all sectors other than banking, insurance and equity investments, that claim to be socially responsible, through an analysis of the redistribution of their created value towards five categories of primary stakeholders, that are: lenders of funds, customers, suppliers, shareholders and employees.